Namudzaj al-Lughah al-'Arabiyyah li Aghrad Muhaddadah: Tashmim al-Mursyidin al-Siyahiyyin al-Nathiqin bi Lughah al-â€˜Arabiyyah - Amalia, Dian Risky; Yasmar, Renti; Wargadinata, Wildana; Nurhadi, Nurhadi (Arabiyatuna: Jurnal Bahasa Arab, 2023)
This study aims to work on an ASP (Arabic for Specific Purposes) model designed by Arabic-speaking tour guides. As the background, the increase in the number of tourists coming from the Middle East from year to year shows that Indonesian tourism is in high demand, but it seems that the tourism industry in Indonesia does not expect the number of tourists coming from the Middle East to increase because both the government and the private sector are doing more promotion. Arabic language teaching especially in the realm of tourism becomes the center of this study. This research uses a qualitative approach, and the data collection techniques subsume interviews, observations, and documentation from the implementation of ASP training in Jogjakarta. This study has found that the ASP Model for tourism is student-centered learning with practical-based learning strategies considering needs analysis and prior information. ASP model is prepared for students at an advanced level. Students are also familiar with the basics of tourist guidance and interpretation skills in tourism. The foregoing is underlined by a notion that the teaching of ASP for tourism is inseparable from fluency of speech and comfortable statements.Â Â